2020
DOI: 10.1002/jpen.2011
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Complications Associated with Parenteral Nutrition in Preterm Infants < 32 Weeks with a Mixed Oil Lipid Emulsion vs a Soybean Oil Lipid Emulsion in a Level IV Neonatal Intensive Care Unit

Abstract: Background Parenteral nutrition (PN) is crucial for the improvement of long‐term outcomes in very low birth weight (VLBW) neonates. Lipid injectable emulsions are a key component of PN, as they contain essential fatty acids and provide energy critical for brain growth. Prolonged administration increases risk of intestinal failure‐associated liver disease, including cholestasis, and other complications. Methods This is a retrospective, quasi‐experimental cohort study of 215 VLBW neonates. The primary outcome wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
(107 reference statements)
1
4
0
Order By: Relevance
“…However, only one randomized controlled trial showed that cholestasis was significantly lower in fish oil–containing ILEs (0% vs 18.2%; P = 0.011) in VLBW infants than in the pure soybean oil emulsion 23 . Recently, published retrospective studies showed that there was no significant difference in the incidence of PNAC in VLBW infants between SMOFlipid and Intralipid, 15,24–26 which is consistent with the conclusions drawn in this study. In the current study, which reported the incidence of cholestasis, no further comparisons were made between the two ILEs in VLBW infants.…”
Section: Discussionsupporting
confidence: 90%
“…However, only one randomized controlled trial showed that cholestasis was significantly lower in fish oil–containing ILEs (0% vs 18.2%; P = 0.011) in VLBW infants than in the pure soybean oil emulsion 23 . Recently, published retrospective studies showed that there was no significant difference in the incidence of PNAC in VLBW infants between SMOFlipid and Intralipid, 15,24–26 which is consistent with the conclusions drawn in this study. In the current study, which reported the incidence of cholestasis, no further comparisons were made between the two ILEs in VLBW infants.…”
Section: Discussionsupporting
confidence: 90%
“…However, they did not focus on VLBW and ELBW infants. More recently, original studies including observational studies [ 32 39 ] and RCTs [ 19 29 ] have begun to focus on the prevention effect of fish oil-containing lipid emulsions on VLBW infants, but their results vary. Our meta-analysis provides an objective argument that fish-oil containing lipid emulsions can decrease occurrence of PNAC in VLBW infants.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from literature in adult patients, a recent report examined differences in the incidence of varied complications associated with MO‐IFE versus SO‐IFE in NICU patients 37 . Of these, the incidence of sepsis was reduced in patients who received MO‐IFE compared to SO‐IFE.…”
Section: Discussionmentioning
confidence: 99%